Analysis of the Impact of Spare Parts Availability on Information Flow in The Supply Chain - Karolina KOLINSKA (Communications of International Proceedings, 2022)
Analysis of management and information flow in an enterprise and its supply chain is an extremely complex issue. The specificity of manufacturing companies, which guarantee the continuity of production by ensuring the availability of spare parts for production needs, is a very complex research problem. It includes in its analytical scope the process of material supply, for elements whose consumption (spoilage) is very difficult to plan. Classical stock management does not guarantee integrated data and information flow in the field of spare parts, which creates the necessity to identify factors and data that determine the information flow on spare parts availability. The aim of this paper is to identify the key factors determining the availability of spare parts in the supply chain of manufacturing companies, using the methodology of network thinking. The research is complemented by the analysis of factors determining the availability of spare parts. The research presented in this paper is a result of research and implementation works carried out by the author.
Keywords: spare parts availability; information flow efficiency; spare parts management